Development Of Adobe Flash Learning Media In Increasing The Quality Of The 8th Grade Madrasah Tsanawiyah Darul Faizin - Iis Makhisoh (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2019)
Speaking is one of the main components in language learning. Speaking is the most important element in the four Arabic language skills, speaking skills are a barometer of the success of Arabic language teaching, so that the success of a language teaching is seen from the ability of students to speak, if students speak fluently in accordance with their desires, then a teaching is successful. Among the main objectives in learning Arabic for non native speakers is to improve the ability of students to be able to pronounce the language well and be able to communicate with native Arabic speakers well and spontaneity. From the observations of researchers and interviews with Arabic language teachers, that some students in the eighth grade Madrasah Tsanawiyah Darul Faizin Assalafiyah Catak Gayam Mojowarno Jombang are unable to dialogue using Arabic on Arabic subjects, they have difficulty in making correct sentences, and when they dialogue using Arabic, then they speak not fluently. One reason is the lack of vocabulary they mastered, and also there is no media that can make them speak Arabic. Furthermore, based on the facts of the problem above, the formulation of this research is to develop Flash-based media or better known as Adobe Flash, and measure the extent to which the effectiveness of the application of the media in improving the speaking skills of eighth grade students of Madrasah Tsanawiyah Darul Faizin Assalafiyah Catak Gayam Mojowarno Jombang in the academic year 2019/2020in semester one. The approach used in this study is research and development (R&D) using the "t" test formula. The sample design used was "One group pretest and post test design" in one class of 25 students. The results showed that the application of Adobe Flash Media was proven to be effective in improving the speaking skills of eighth grade students of Madrasah Tsanawiyah Darul Faizin Assalafiyah Catak Gayam Mojowarno Jombang. This can be seen from the increase in the value of the pre-test and post-test results, in the pre-test the average value was 62.2%, and in the post-test it increased to an average of 84.16%.